IMPLEMENTASI SARANA DAN PRASARANA PERPUSTAKAAN SMP NEGERI 1 SIRAH PULAU PADANG TERHADAP PENGARUH MINAT KUNJUNG SISWA - Oktaviana, Dita (Pusat Studi Ekonomi Publikasi Ilmiah dan Pengembangan SDM Azramedia indonesia, 2024)
As we know information cannot be separated from humans for the sake of daily survival, information is also available in various forms and places of provision, one of which is the library. Libraries are indistinguishable from schools because they influence teaching and learning activities. In this article, the author uses a qualitative approach method so as to produce data that has been analyzed by the author regarding the reasons why the implementation of library facilities and infrastructure influences student interest in visiting SMP N 1 Sirah Pulau Padang. The results showed that the data obtained at the SMP N 1 SP library. Padang as a whole regarding facilities and infrastructure is quite complete. Starting from the library room which is quite spacious when compared to other school libraries in this sirah padang island area, besides that, the interior arrangement is quite appropriate to be called a library. The arrangement and arrangement of the books are in accordance with their respective classification numbers, it's just that the pasting of the book numbers has not been evenly distributed, only on certain books that have book numbers on the back of the book.